Survey on multi-channel schemes in wireless body area network - Raj Kumar Naik, M; Samundiswary, P (International Journal of Engineering and Technology, 2018)
The evolution and empowerment of Wireless Body Area Network (WBAN) is achieved through the rapid advancement in the wireless communication technologies. The use of different kinds of sensors which are utilized in the health care applications for patient monitoring are helped for diagnosis of life threatening disease which can be improved by using WBAN. These wearable systems help in controlling the life of patient is as they play essential role to save patientâ€™s life. In recent past, the system architecture is constructed for WBAN for monitoring of health care application and enhancing the technical requirements in a WBAN network. Although, Wireless Body Area Networks (WBAN) is one of the emanate technology which utilizes the patient health condition for monitoring in real time, several issues that are faced by WBAN are Quality of Service (QoS), security, data loss, authentication, channel issues and energy efficiency. Most of the WBANs utilizes wireless channel for process of communication in which these typical sensors with single transceiver device transmits the information with low power by utilizing a single channel using Medium Access Control (MAC) layer in WBAN. However, the degradation in performance of these devices is high when the sensors density is increased. The solution to overcome this performance degradation is carried out by making use of multiple channels, due to which the channels are optimally utilized and the cooperation among the sensor nodes is achieved. In this paper, the survey of different protocols used for WBAN under different channel conditions is discussed in WBANs with its merits.Â Â Â